Ante el espejo del triunfo. La élite ítalo-uruguaya en la heremografía de entreguerras - Bresciano, Juan Andrés (Confluenze. Rivista di Studi Iberoamericani, 2017)
During the inter-war period, a prosperous elite was consolidated within the Italo-Uruguayan community. In its social consecration, two publications plaid a significant role: L’Italiano, a weekly journal that sympathized with the fascist regime, and La Patria Italiana en el Uruguay, a magazine committed to the defense of democracy. Based on a study of both, this article aims to identify what kind of criteria, factors and circumstances affected the publicity that placed the "notables" of the immigrant community before the mirror of triumph.